The Experiences of Business Students with Mothers in Food Processing and Marketing - Estoconing, Roberto A. (Silliman Journal, 2022)
This article describes how the primary goal of the community activities of the business students was realized, i.e. to promote self-help among the residents by teaching some ways by which they could improve their income. They first conducted a community resource inventory to identify available and existing resources which was used as basis for the development of a livelihood project. The students worked directly with mothers who decided to engage in food processing and marketing considering the available resources and skills in the community. The mothers were also organized into an association and eventually into a cooperative with the help of the Social Work students. This field work experience with the mothers taught the business students the values of developing will and perseverance, learning to socially adjust, understanding social realities, cultivating a positive attitude, and gaining a sense of satisfaction from their social engagement.